Organisational and legal foundations of the activity of Ukrainian police officers to restore law and order on the liberated territory from German invaders in 1943-1945 - Тимченко, А. П. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
The article describes the operational situation in the areas liberated from the invaders of Ukraine. Tells what a zakonnisi and order. Much attention is paid on time taken by the authorities and management laws and regulations, which were posed specific challenges to restore order in the liberated territory. Deals with the organizational activities of the police to implement the requirements specified in Article regulations, which was aimed at recovery and on liberated territory law and order. The author highlights the main activities of the police, which contributed to hover proper law and order, to achieve good results in the fight against crime.